Beta-blockers in Musicians: Mechanisms, Clinical Evidence, Prevalence, and Ethical Parallels with Anti-Doping Regulation in Precision Sports – A Narrative Review - Chmiela, Mateusz; Lachowska, Ewelina Maria; Bartkiewicz, Patrycja Anna; Baran, Wojciech Przemysław; Janiszewski, Cyprian Mariusz; Ratajczyk, Oskar (Quality in Sport, 2026)
Background: Music Performance Anxiety is a frequent problem among musicians. Beta-blockers, especially propranolol, are used by some performers to reduce somatic symptoms of stage fright. Aim: This narrative review aimed to analyse the mechanisms, clinical evidence, prevalence, safety and ethical implications of beta-blocker use among musicians, including parallels with anti-doping regulation in precision sports. Material and methods: A targeted literature search was conducted using PubMed, Google Scholar, JSTOR and ResearchGate. Clinical studies, surveys, reviews, regulatory documents and bioethical analyses concerning beta-blockers, Music Performance Anxiety, stage fright and performance enhancement were included. Results: Beta-blockers may reduce peripheral manifestations of sympathetic arousal and may be useful in selected performance situations. However, the available evidence remains limited by small samples, older study designs and heterogeneous outcome measures. Survey data indicate that beta-blocker use occurs among musicians, particularly in auditions and other high-pressure performances. Their use also raises safety concerns and ethical questions about the boundary between therapy, symptom control and performance enhancement. Conclusions: The available evidence suggests that beta-blockers may have a limited role in selected musicians, mainly as a short-term option for reducing somatic symptoms of stage fright. They should not be seen as a routine or complete treatment for Music Performance Anxiety. Their use, particularly before auditions and other high-pressure situations, raises questions about safety, medical supervision and fairness. The parallel with precision sports, where beta-blockers are formally regulated, further highlights the ethical complexity of their use in music. Therefore, beta-blocker use in musicians should be approached cautiously, with clear education and individual medical assessment.